Fertility Decline in Pakistan 1980-2006 : A Case Study - World Bank (World Bank, Washington, DC, 2017)
Pakistan was selected as a case study because of its estimated 40 percent decline in fertility between 1980 and 2006. Pakistan's high fertility rate began to decline gradually after the late 1980s and has continued to fall since then, though progress has been uneven and there have been signs of a slowdown in recent years. Unlike the other four case study countries (Algeria, Botswana, Iran, and Nicaragua), the history of fertility reduction in Pakistan has not been an overwhelming success story but rather a story of challenges, partial responses, and shortcomings that offer abundant lessons for other high-fertility countries as well as planners in Pakistan.